Telemedicine pada Layanan Tuberkulosis (Literature Review) - Siti Muhimatul Munawaroh; Vetty Yulianty Permanasari (Jurnal Informatika Terpadu, 2023)
The current Covid-19 pandemic has restricted people's movements to access health services. This has resulted in reduced access to tuberculosis treatment and has resulted in increased mortality. The government has advocated using digital tools and technologies such as telemedicine for patient care. This research aims to find out how telemedicine is applied to tuberculosis services. This study uses the Systematic Literature Review methodology with scientific article publication data sources from the Google Scholar, PubMed, ScienceDirect, and ProQuest databases. From the 6440 articles obtained at the start of the search, in the end, 18 articles met this study's inclusion and exclusion criteria. Results: The implementation of telemedicine in tuberculosis services is carried out using DOT (Direct Observation Treatment) therapy using Video or vDOT (Video Direct Observation Treatment), while other telemedicine activities are carried out via direct telephone, sending voice text messages periodically for patient reminders, vDOT is carried out online synchronous via uploads or asynchronous via video recording. The telemedicine platform is helpful for health workers in tackling and preventing tuberculosis which requires intensive monitoring of patients so that patients can be monitored regularly, reducing drug withdrawal patients and increasing the success of tuberculosis treatment. There are opportunities for the development of telemedicine applications in Indonesia that focus on the use of vDOT.